Domestic Tourists' Perceptions of Education-Based Tourism Products at Bali Bird Park - Yosita, Ni Kadek; Tirtawati, Ni Made; Lilasari, Luh Nyoman Tri (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Tourist perception is a tourist's view, understanding of a tourist towards a tourist destination. Educational tourism products are activities that integrate learning experiences with recreation to provide added value to tourists. This study was conducted at Bali Bird Park with the aim of determining the perception of domestic tourists towards educational tourism products at Bali Bird Park. This study is quantitative with a sample of 100 respondents who have visited Bali Bird. The data obtained were processed using SPSS with Descriptive Analysis, Validity Test and Reliability Test. Based on the average of each variable, the accessibility variable has the highest average value of 4.54 with a very good category. Based on the accessibility variable indicator, tourists really like access to the Bali Bird Park tourist attraction because it makes it easy for tourists to find the location of Bali Bird Park. While the variable that has the lowest average value is the price variable with an average of 4.13 in the good category. This is because the prices given are still quite expensive such as food and drinks due to the lack of restaurant facilities or food stands.